Perbedaan Tingkat Pengetahuan dan Sikap Ibu Terhadap Kelengkapan Imunisasi Dasar Wajib di Wilayah Kerja Puskesmas Hutarakyat Kecamatan Sidikalang Kabupaten Dairi Tahun 2019 - Regina Saely Sitanggang; Ade Pryta Simaremare; Saharnaul J Verawaty Simorangkir (Nommensen Journal of Medicine, 2019)
Immunization is an effort to raise / enhance immunity against a disease actively, if one day body is exposed to the disease, it will not get sick or it will get mild illness. According to the 2013 and 2018 Riskesdas data on complete obligatory basic immunization coverage in Indonesia it was found decrease from 59.2% to 57.9%. Obligatory basic immunization coverage in Dairi Regency in 2016 - 2017 has decreased, in 2016 (83.7%) and 2017 (81.3%). The objective of this study was to determine the differences in the level of knowledge and attitudes of mothers with the completeness of obligatory basic immunizations in the working area of ​​the Hutarakyat Health Center in 2019. This was an analytical study with a case control design. The study sample was 76 respondents taken by consecutive sampling. Data collected is using questionnaire. The results of this study showed that of 76 respondents, mothers who brought their babies for immunization in 2019 had the most adulthood (77.6%), had higher education (69.7%), had a non-working status (60.5%), had good knowledge (65.9%), and had a positive attitude (62.5%). Toward immunization there were significant differences in the level of knowledge and attitudes of mothers towards the completeness of obligatoty basic immunization. There were differences in the level of knowledge and attitudes of mothers with the completeness of obligatory basic immunizations.